2019
DOI: 10.1111/jon.12604
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography Monitoring of Optic Nerve Sheath Diameter and Retinal Vessels in Patients with Cerebral Hemorrhage

Abstract: BACKGROUND AND PURPOSE Evaluation of the diagnostic accuracy of optic nerve sheath diameter (ONSD) and Doppler indices of central retinal arteries and veins for the detection of increased intracranial pressure (ICP) in intracerebral hemorrhage (ICH) and of the usefulness of a second assessment of these variables in the monitoring of ICH. METHODS A total of 46 acute ICH patients with (group 1, n = 25) and without (group 2, n = 21) clinical and radiological computed tomography signs of raised ICP and 40 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
(73 reference statements)
1
14
0
1
Order By: Relevance
“…They emphasize that relative enlargement of the ONSD is a more sensitive indicator of raised ICP than the absolute ONSD value [27]. Naldi et al also investigated ONSD in patients with ICH and have shown that the second assessment of ONSD measurements may be useful in identifying patients with the persistency of elevated ICP [28]. Both studies have indicated the need for more research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…They emphasize that relative enlargement of the ONSD is a more sensitive indicator of raised ICP than the absolute ONSD value [27]. Naldi et al also investigated ONSD in patients with ICH and have shown that the second assessment of ONSD measurements may be useful in identifying patients with the persistency of elevated ICP [28]. Both studies have indicated the need for more research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies stated that ONSD is over 5 mm when ICP is over 20 mmHg; ONSD of patients with TBI elevated up to 6.3 to 6.4 mm 29,30,31 . Moreover, ONSD is higher in patients with lower GCS, higher ICP, and in those who die from the injury 7,31,32,33 .…”
Section: Onsdmentioning
confidence: 94%
“…In recent years, development of digital imaging technology, especially the neonatal digital wide-area fundus imaging system made it possible to conduct screening for neonatal eye diseases in ophthalmic hospitals [28,29]. Neonatal digital wide-area fundus imaging systems overcome some of the shortcomings of traditional inspection equipment.…”
Section: Discussionmentioning
confidence: 99%